PENGGUNAAN MEDIA MAGIC MIRROR UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA DISLEKSIA DI SEKOLAH DASAR LAMPUNG UTARA - Maya Setia Priyadi; Della Monica; Devy Aulia Saputri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to test the effectiveness of Magic Mirror media in improving the reading skills of dyslexic students in North Lampung elementary schools. This media is designed to help students recognize letters that are often reversed, such as “b” and “d”, “p” and “q”, and “m” and “w”. The research method used a descriptive quantitative approach with data from observations and interviews in three elementary schools: SDN 3 Sindang Sari, SDN Gunung Raja, and SDN Labuhan Ratu Besar. The results showed an average increase in students' reading ability of 34.40% after the use of Magic Mirror. A total of 80% of students experienced significant improvement, while the other 20% showed very significant improvement. There were no students who experienced low improvement. Magic Mirror proved to be effective in helping dyslexic students overcome reading difficulties, so it is expected to support their smooth education and social interaction. This study recommends the wider application of Magic Mirror in primary schools to assist dyslexic students' learning.